The Dichotomy of Proliferating Information Technology in Globalization of Education: A Case Study - Sri Herminingrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
The Information Technology (IT) proliferation path cannot be separated from the role of American young entrepreneurs who generate revolutionary change in global information system. This modern existence, of course, leads to the socio-cultural phenomena encompassing dichotomous trends in many aspects of Indonesian daily lives, not to mention in education world. Scrutinizing the data obtained from a one-semester direct observation, structured interview, and questionnaire distribution to 586 students of 11 faculties at Universitas Brawijaya is used as the base of a case study. By employing qualitative method, therefore, the study aims to provide insights about the merits and demerits of the use of IT in globalization of education, which is commonly happening in Indonesia within the last decade. The result shows that the dependence of students as Indonesian digital citizen on the internet-based information tends to impact negatively on the basic values of education, such as influencing the students to be narrow-minded, self-centered, and preferring to gain instant results.